Epidemiology of Campylobacter jejuni in raccoons (Procyon lotor) on swine farms and in conservation areas in southern Ontario. (23rd November 2020) - Vogt, Nadine A.; Pearl, David L.; Taboada, Eduardo N.; Mutschall, Steven K.; Bondo, Kristin J.; Jardine, Claire M.
Abstract: Campylobacter is a leading cause of foodborne illness in humans worldwide. Sources of infection are often difficult to identify, and are, generally, poorly understood. Recent work suggests that wildlife may represent a source of Campylobacter for human infections. Using a repeated cross‐sectional study design, raccoons were trapped on five swine farms and five conservation areas in southern Ontario from 2011 to 2013. Our objectives were to: (a) assess the impact of seasonal, climatic, location, annual and raccoon demographic factors on the occurrence of Campylobacter jejuni in these animals; and (b) identify clusters of C. jejuni in space, time and space‐time using spatial scan statistics. Multi‐level multivariable logistic regression was used to examine the odds of isolating C. jejuni, with site and animal modelled as random intercepts. The following independent variables were examined: raccoon age and sex, year, location type, season, temperature and rainfall. A total of 1, 096 samples were obtained from 627 raccoons; 46.3% were positive for C. jejuni . The following interactions and their main effects were significant ( p  < .05) and retained in the final model: season × temperature, year × rainfall, year × temperature. Based on the results from our multivariable model and spatial scan statistics, climatic variables (i.e. rainfall, temperature and season) were associated with the carriage of C. jejuni by raccoons, but the effects were not consistent, and varied by location and year. Although raccoons may pose a zoonotic risk due to their carriage of Campylobacter, further work is required to characterize the transmission and movement of this microorganism within the ecosystem.